ETHICAL USE OF INFORMATION AND FIGHT AGAINST PLAGIARISM: looking into brazilian university libraries - Menezes Alves, Ana Paula [UNESP]; Silva Casarin, Helen de Castro [UNESP]; Fernandez-Molina, Juan-Carlos (Univ Federal Campina Grande, 2016)
We address the issue academic plagiarism prevention from a discussion that brings together the ethical use of information in scientific production, the development of the information literacy and the actions taken by university libraries to prevent and fight against the problem. We employed a search for information contained in the institutional websites of libraries to identify actions taken for guidance and/or the fight against academic plagiarism. We evaluated the websites of 10 Brazilian public universities best classified at the Ranking Universitario da Folha (RUF) of 2014. The search was systematized through a type of leveling developed by the researchers, which allowed to indicate the quantity, quality and type of information that is displayed at the libraries evaluated websites. As a result, we observed that there is still little information that depicts actions regarding information literacy, plagiarism and ethical aspects within academic libraries. The data gathered portray that more than a half of the units have only basic information such as research techniques, addressing only part of the concept of information literacy; almost all libraries, with rare exceptions, do not mention information regarding the ethical use of information and plagiarism, respectively. The type of information presented regards the mentioning of copyright law, reprography, plagiarism detection software and/or punitive action and not effective actions to educate the individuals for the ethical use of information and for combating plagiarism.
Keywords: Academic Plagiarism; Information literacy; Ethical aspects; Academic honesty